INCREASING YOUTH KNOWLEDGE IN HANDLING SYNCOPE CASES IN STUDENTS OF THE SENIOR HIGH SCHOOL OF ANTARTIKA, BUDURAN, SIDOARJO - Marlita Dewi Lestari; Pinik Monika; Elsa Meilani Ekasari; Mirna Paramitha Songupnuan; Fausta Fadir Syair; Sri Wahyuningsih; Indriani Cahya Ningrum (Community Service Journal of Indonesia, 2020)
Health promotion activities about first aid for syncope cases of the Senior High School of Antartika, Buduran, Sidoarjo is one form of community service in the form of counseling aimed at increasing children's knowledge about how first aid in syncope besides fatigue, syncope can also be caused by overheating, being trapped in space closed to lack of oxygen, shocked or surprised. The implementation of these activities on November 20, 2019 took place at the Senior High School of Antartika, Buduran, Sidoarjo. The target is Senior High School students of Antartika, Buduran, Sidoarjo. Before the activity is carried out, there is a process of compiling the activity for approximately 2 weeks before the activity is carried out, starting from determining the theme of counseling to submitting licensing to the parties concerned. As a form of evaluation, the activity was attended by 30 class X students, participants took part in the activity happily and looked very enthusiastic, health promotion activities could run on time and smoothly. Keywords: Knowledge, syncope cases, first aid health promotion.